Epidemiological Patterns Of Chronic Diseases Identified In Primary Care And Their Public Health Implications (The Review of Diabetic Studies, 2025)
Chronic diseases constitute the dominant global health burden, accounting for the majority of morbidity, mortality, disability, and healthcare expenditure worldwide. While hospital-based data traditionally inform disease burden estimates, the epidemiological reality of chronic disease is most accurately observed within primary care, where conditions are first detected, risk factors accumulate, multimorbidity emerges, and long-term disease trajectories unfold. This comprehensive narrative review examines epidemiological patterns of major chronic diseases as identified in primary care settings, including cardiovascular disease, diabetes mellitus, chronic respiratory disease, mental health disorders, and musculoskeletal conditions. Drawing on international primary care–based evidence, the review explores prevalence trends, demographic gradients, multimorbidity clustering, and socioeconomic determinants, and critically analyzes their implications for public health surveillance, prevention strategies, and health system design. The findings emphasize that primary care epidemiology provides indispensable intelligence for population health planning and underscores the necessity of integrating primary care data into public health decision-making frameworks.